Risk, balanced skills and entrepreneurship - Chihmao Hsieh; Simon C. Parker; Mirjam van Praag (Institute for the Study of Labor (IZA), 2011)
This paper proposes that risk aversion encourages individuals to invest in balanced skill profiles, making them more likely to become entrepreneurs. By not having taken this possible linkage into account, previous research has underestimated the impacts both of risk aversion and balanced skills on the likelihood individuals choose entrepreneurship. Data on Dutch university graduates provides evidence which supports this contention. It thereby raises the possibility that even risk-averse people might be suited to entrepreneurship; and it may also help explain why prior research has generated mixed evidence about the effects of risk aversion on selection into entrepreneurship.
urn:nbn:de:101:1-201201107499
Keywords: D81; J24; L26; M13; 330; entrepreneurship; jack-of-all-trades; risk; human capital; occupational choice; Unternehmer; Selbstständige; Risikoaversion; Bildungsverhalten; Berufswahl; Niederlande